1988
DOI: 10.1021/bi00409a046
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-induced lateral phase separation in phosphatidic acid/phosphatidylcholine monolayers as revealed by fluorescence microscopy

Abstract: Phase separation in mixed monolayers of phosphatidylcholine (PC) and pyrene-labeled phosphatidic acid (PA) was observed by fluorescence microscopy on an air/water interface as a function of subphase Ca2+ concentration and lateral packing pressure of the film. Below 45 mN m-1 and in the absence of Ca2+ no indications of phase immiscibility were observed. Addition of 1 mM Ca2+ caused extensive phase separation, which was evident immediately after spreading of the film. Further increase in Ca2+ concentration up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 36 publications
(42 reference statements)
2
27
0
Order By: Relevance
“…The behaviour vs. wavelength is qualitatively similar to that observed in the liquid-crystalline phase and quite different from that observed in the presence of coexisting domains of the two phases. Several recent articles reported on the progressive removal of phospholipid phase transition by cholesterol addition [32][33][34]. Many groups are concerned with the occurrence of phospholipid domains containing different cholesterol concentrations in model systems [21][22][23][24]35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The behaviour vs. wavelength is qualitatively similar to that observed in the liquid-crystalline phase and quite different from that observed in the presence of coexisting domains of the two phases. Several recent articles reported on the progressive removal of phospholipid phase transition by cholesterol addition [32][33][34]. Many groups are concerned with the occurrence of phospholipid domains containing different cholesterol concentrations in model systems [21][22][23][24]35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2ϩ ions bind to acidic phospholipids and are known to have a strong influence on their phase behavior and organization (Galla and Sackmann, 1975;Hartmann et al, 1977;Eklund et al, 1988Eklund et al, , 1991. Binding of adriamycin to LUVs (X PG ϭ 0.25) was subsequently measured at increasing [CaCl 2 ].…”
Section: Dependence On the Content Of Acidic Phospholipid In Liposomesmentioning
confidence: 99%
“…There is evidence of lateral heterogeneity in lipid membranes being induced by alcohol (Rowe, 1987;Mou et al, 1994). In binary membranes containing charged (anionic or cationic) species, phase separation can be induced by Ca 2ϩ (Galla and Sackmann, 1975;Eklund et al, 1988), polycations (Hartmann et al, 1977;Eklund and Kinnunen, 1986), DNA , electric fields (Lee et al, 1994;Lee and McConnell, 1995;Söderlund et al, 1997), and pH (Tilcock and Cullis, 1981). Likewise, several cationic peripheral proteins induce the segregation of acidic phospholipids .…”
Section: Introductionmentioning
confidence: 99%
“…To date, most investigations of divalent cation- and protein-induced PS microdomains have either relied on perturbative methods or focused on bulk characteristics such as surface pressure (1517). For instance, it has been demonstrated that membrane-binding proteins, such as annexin A5 and 2, in concert with plasma concentrations of Ca 2+ induce the lateral organization of anionic phospholipids such as PS, phosphatidic acid (PA) and phosphatidylinositol (4,5)-bisphosphate (PIP 2 ) (16, 18, 19). Recently, fluorescence microscopy has revealed that plasma Ca 2+ concentrations induce clustering of PIP 2 into sub-micrometer domains, but no such effect was observed for PS (20).…”
mentioning
confidence: 99%